Factors that influence general medical practitioners in South Africa to prescribe branded or generic medicine - Cutten, Natalie (My University, 2013)
The upcoming implementation of the National Health Insurance coverage presents the possibility that there will be increased consumption of prescription medications in South Africa. The majority of general practitioners practising in South Africa are working in the private sector; therefore this sector still has a strong value proposition amongst pharmaceutical producers. In order to leverage profitability through pharmaceutical detailing targeted at the prescribing doctor within the private sector, there is a need to understand what factors influence the prescription decision. A survey using a modified five point Likert scale was developed in order to ascertain what factors influence the prescription decision. An online survey using Med pages database, as well as a paper based survey distributed at a continuous medical education event, was used to obtain data. A quantitative conjoint design was used to ascertain what factors influence the prescription decision. The conjoint average importances demonstrated that cost was the most important factor within the prescription decision; followed by attitude to generics; specialist recommendations; shared decision making; and finally pharmaceutical promotions. It was also found general practitioners who practice with colleagues that recommend a branded medication are significantly influenced in terms of their prescribing. There is an opportunity for both generic and branded manufacturers to leverage profitability through prescribing general practitioners within the private sector in South Africa. There is a need for generic manufacturers to produce quality products, and to proposition consumers and prescriber whether it is necessary to pay a premium for a medication, when a generic of the same quality can be obtained at a lower price. Branded manufacturers need to focus marketing detailing efforts towards opinion leaders such as specialists, and general practitioners that practice in partnerships, in order to maximise returns through multiplier effects.
MBA thesis
Keywords: Medicine, Branded; Medicine, Generic